JALALUDDIN RAKHMAT DAN PEMIKIRAN SUFISTIKNYA - Muhammad Muhammad (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
Jalaluddin Rakhmat, known as Kang Jalal, is a brilliant Muslim intellectual and intellectual, has sharp reasoning and can speak across disciplines, not only in communication, but also in various other disciplines such as political science, philosophy and Islamic sciences in detail and in depth. The ideas and thoughts put forward by Jalal on various occasions have become the attention and study material of various groups, including Muslim scholars, bureaucrats, politicians and intellectuals themselves. Jalal's ability to adopt various scientific disciplines has received recognition from other Muslim scholars and intellectuals, including the younger generation who want to broaden their horizons in various fields of human life, especially in the field of Islamic science. Jalal is considered as an ideal Muslim intellectual figure, with many ideas, forward thinking and his ideas become valuable discourses and contributions in solving problems and fostering a society that is developing widely.Keywords: Jalaluddin Rakhmat, Sufistik.